Development and Characterization of Seashore Paspalum SSR Markers. Issue 6 (1st November 2013) - Harris‐Shultz, Karen; Raymer, Paul; Scheffler, Brian E.; Arias, Renée S.
ABSTRACT: The increasing use of secondary water sources for irrigation, which is highly linked to salinization, creates a demand for salt tolerant turf. Seashore paspalum ( Paspalum vaginatum Swartz) is a warm‐season turfgrass that survives in sand dunes along coastal sites, brackish ponds, and in estuaries. Some seashore paspalum accessions and cultivars are far more salt tolerant than others. To identify genetic regions that are associated with salt tolerance, molecular tools must be developed. In this study, genomic libraries, enriched for microsatellites, were generated using the salt tolerant accession HI33. High throughput sequencing and subsequent assembling of these libraries resulted in 18, 967 contigs and 158, 595 singletons. The number of simple sequence repeats (SSR) detected in contigs and in singletons was 3511 and 31, 949, respectively, and the number of primer sets designed within each group was 937 and 1667. A total of 80 SSR markers, including five markers previously developed, were used to assess genetic relationships among 18 Paspalum accessions. Two major clusters were identified from the seashore paspalum accessions. Accessions that are likely polyploids, all with coarse leaves, grouped together whereas accessions with fine‐to mid‐fine leaves formed a second group. Furthermore, 33 seashore paspalum SSR markers cross‐amplified in bahiagrass ( Paspalum notatum Flugge) and these markers can be a useful tool in this species.